Emotion Norms, Display Rules, and Regulation in the Akan Society of Ghana: An Exploration Using Proverbs - Dzokoto, Vivian A.; Osei-Tutu, Annabella; Kyei, Jane J.; Twum-Asante, Maxwell; Attah, Dzifa A.; Ahorsu, Daniel K. (Frontiers in Psychology, 2018)
Proverbs are widely used by the Akan of West Africa. The current study thematically analyzed an Akan proverb compendium for proverbs containing emotion references. Of the identified proverbs, a focus on negative emotions was most typical. Emotion-focused proverbs highlighted four emotion regulation strategies: change in cognition, response modulation, situation modification, and situation selection. A subset of proverbs addressed emotion display rules restricting the expression of emotions such as pride, and emotional contagion associated with emotions such as shame. Additional themes including: social context influences on the expression and experience of emotion; expectations of emotion limits; as well as the nature of emotions were present in the proverb collection. In general, Akan emotion-related proverbs stress individual-level responsibility for affect regulation in interpersonal interactions and societal contexts.